Fisikokimia, Mikrobiologi dan Organoleptik Yogurt Probiotik dengan Penambahan Buah merah (Pandanus conodeous L.) - H. A. Jonathan; I. N. Fitriawati; I. I. Arief; M. S. Soenarno; R. H. Mulyono (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2022)
Yogurt can be made from homogenized milk, low-fat milk or skimmed milk with the addition of powdered milk. Starter culture commonly used in yogurt is Lactobacillus bulgaricus and Streptococcus thermophillus can not survive in environments with high acidity, so probiotics needed. One of the fruits that can be used in the process of making yogurt is red fruit (Pandanus Conoideus L). The purpose of this study was to analyze the physical and organoleptic properties of probiotic yogurt given the addition of red fruit. The observed physical characteristics consist of pH, viscosity, total acid concentration and water activity (aw) and organoleptic arachnids observed consisting of color, flavour, aroma and consistency. This research was using a complete randomized design (RAL). The results showed that the addition of red fruit has a real effect (P<0.05) on pH, viscosity and total acid titrated and organoleptic test shows the addition of red fruit has a noticeable effect on color, flavour, aroma and viscosity in hedonic quality tests, then in hedonic tests affect aroma and flavour. Based on the results of yogurt testing with the addition of 2.5% this is the closest to control and acceptable to Indonesian National Standards (SNI).